Hereditatis petitio from an active methodological proposal - Elisa Muñoz Catalán (Universitat Politècnica de València, 2014)
With the active methodological proposal that we show about hereditatis petitio based on the case method, we try to justify how the resolution in classroom of the hereditary real problems regulated from the Roman Law, it serves us to explain theoretical contents of this subject, which traditionally has been taught through master classes at spanish Universities, and also it helps us to understand controversial cases emerged after the current economic crisis, around: the testamentary succession, the petition and subsequent acceptance or renunciation of inheritance, well as potential heirs or substitutes called to inherit after the death of the deceased, already exists an active (property or rights) or passive (duties or debts) mass. Therefore, following the methodological requirements of the EEES in the curriculum of Law Degree where the student is the protagonist of his teachinglearning process we will demonstrate that, with the implementation of this case belonging to the consequences of hereditatis petitio, we approach the university students to roman casuistry and this serves to them to consolidate the contents explained at the beginning of the sessions; understanding that important thing is not a single solution but rather give reason getting through group discussions and self-study, a deeper knowledge of the rules and institutions applicable. We understand, in short, that only in this way they will achieve a number of useful general and specific skills, when they finish the Degree and they face the difficulties of the labor market.